Forkhead box class O family member proteins: The biology and pathophysiological roles in diabetes. Issue 6 (19th April 2017) - Tsuchiya, Kyoichiro; Ogawa, Yoshihiro
Abstract : Forkhead box class O family member proteins (FoxOs) of transcription factors are essential regulators of cellular homeostasis, including glucose and lipid metabolism, oxidative stress response and redox signaling, cell cycle progression and apoptosis. We summarize the basic biology and pathophysiological significance of FoxOs in diabetes. Abstract: Forkhead box class O family member proteins (FoxOs) of transcription factors are essential regulators of cellular homeostasis, including glucose and lipid metabolism, oxidative stress response and redox signaling, cell cycle progression, and apoptosis. Altered FoxO1 expression and activity have been associated with glucose intolerance, dyslipidemia and complications of diabetes. In the liver, they direct carbons to glucose or lipid utilization, thus providing a unifying mechanism for the two abnormalities of the diabetic liver: excessive glucose production, and increased lipid synthesis and secretion. In the pancreas, FoxO1 is necessary to maintain β‐cell differentiation, and could be promising targets for β‐cell regeneration. In endothelial cells, FoxOs strongly promote atherosclerosis through suppressing nitric oxide production and enhancing inflammatory responses. In the present review, we summarize the basic biology and pathophysiological significance of FoxOs in diabetes.